Hormone-Sensitive Gene Signatures in the Mammary Epithelial Cells of Lactating Women With Persistent Low Milk Production. (7th June 2021) - Bernardo, Katherine; Hovey, Russell; Trott, Josephine; Wagner, Erin; Karns, Rebekah; Riddle, Sarah; Thompson, Amy; Ward, Laura; Nommsen-Rivers, Laurie
Abstract: Objectives: Insulin resistance may contribute to the association between maternal obesity and lactation difficulties. Our objective was to examine differential expression of genes involved in insulin-sensitive and prolactin-sensitive signaling in the mammary glands of women with very low, versus sufficient, milk production. Methods: Among a subset of mothers in a study of low milk supply, extracellular mammary epithelial cell mRNA was isolated from fresh milk fat and submitted for RNA-sequencing. Aligned and quantified reads were examined for differentially expressed genes by t-test (DEG, p < 0.05 after false discovery rate adjustment). Insulin signaling and prolactin signaling KEGG pathways, in addition to a hand-curated gene list developed from relevant literature, were used for targeted DEG analysis. Sample size (milk volume range) for the sampled breast was n = 5 for the lowest milk production group [LMP] (0–53 mL/24 h),  versus n = 4 for the highest milk production group [HMP] (422–463 mL/24 h). Clinical measures of metabolic health included BMI and fasting insulin and glucose. Results: All LMP samples were from mothers with obesity and with significantly elevated markers of insulin resistance versus the HMP group (e.g., HOMA-IR 1.7 versus 1.1, p < 0.05). DEG in the LMP group revealed significantly lower insulin-sensitive signaling, including a 2.3-fold decrease in insulin receptor substrate 2 (IRS2), versus HMP. There was no differential expression for genes involved in prolactin signaling, such as the prolactin receptor or JAK2. In LMP versus HMP groups, synthesis of beta-casein (CSN2) was 2.1-fold lower; expression of acetyl-CoA carboxylase 2 (ACACB), a gene downstream of insulin signaling that inhibits fatty acid oxidation, was 3.1-fold lower; and expression of UDP-glucose pyrophosphorylase 2 (UGP2), a rate-limiting gene in lactose synthesis and thus a determinant of milk volume, was 2.7-fold lower. Conclusions: Suppressed milk production by obese, LMP mothers is associated with downregulation of insulin-signaling genes but not hallmark prolactin-signaling genes. Overall, gene expression in the LMP group portrays an insulin-resistant signature in the mammary gland, with downregulation of insulin-sensitive anabolic processes and upregulation of catabolic gene expression. Funding Sources: NIH.